Állami beavatkozás, lokális eladósodás, túlfűtöttség és ezek rendszerbeli okai a globális válság alatt Kínában - Mária Csanádi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
– This paper describes the impact of the global crisis on China, the central and local level government responses and preferences it triggered as well as the consequences these reactions had on national and regional levels. It focuses on the immediate economic and general systemic reasons of the development of local indebtedness and that of the overheating generated by investment. It sheds light on the fact that despite the substantial evolution of the market economy in China, the state interventions to compensate the impact of the crisis activate the general and specific Chinese characteristics of party-states during the process. These specifics will determine the politically rational criteria in the distribution of resources, the accomodating investment behavior of actors and the characteristics of distribution according to the specifics of the Chinese power structure. It is the prevalence of these specific structural characteristics that will cause among others the penomena of local indebtedness, local economic overheating and the hardships in their central control.
Keywords: F5; D78; R58; J08; O15; E24; 330; local indebtedness; crisis; party-state system; resource distribution; state inter-vention; overheating; Wirtschaftskrise; International; Wirkungsanalyse; Sachenrecht; China